Fashion as photograph viewing and reviewing images of fashion - Shinkle, Eugénie 1963- (I.B. Tauris & Co. Ltd, 2008)
Photographic images are a driving force behind the fashion system, and they play a key role in defining global fashion culture. Fashion photography is attracting increasing public attention; it has embraced new image-making technologies, and has shown itself to be a commercially and ideologically powerful medium.This rich and rewarding book combines new critical approaches with views from inside the industry, showing fashion photography to be a complex cultural phenomenon worthy of serious critical attention. It brings together distinguished contributors from the UK, North America, Australia and Europe - including Rankin, Philippe Garner, Penny Martin, Caroline Evans, Eva Respini and Margaret Maynard - to examine the production and consumption of fashion images from the points of view of industry and academia, the museum, the auction house, and the art gallery. Illustrated in black and white and colour, the book discusses key issues in recent fashion photography and establishes a fertile space for new ways of looking to emerge on this dynamic visual form